Prussian Blue‐Derived Synthesis of Hollow Porous Iron Pyrite Nanoparticles as Platinum‐Free Counter Electrodes for Highly Efficient Dye‐Sensitized Solar Cells. Issue 54 (31st July 2017) - Chen, Jeffrey E.; Fan, Miao‐Syuan; Chen, Yen‐Lin; Deng, Yu‐Heng; Kim, Jung Ho; Alamri, Hatem R.; Alothman, Zeid A.; Yamauchi, Yusuke; Ho, Kuo‐Chuan; Wu, Kevin C.‐W.
Abstract: Iron pyrite has long been an attractive material for environmental and energy applications, but is hampered by a lack of control over morphology and purity. Hollow porous iron pyrite nanoparticles were synthesized by a direct sulfurization of iron oxide derived from Prussian blue. The high efficiencies of these hollow porous iron pyrite nanoparticles as effective dye‐sensitized solar cell counter electrodes were demonstrated, with an efficiency of 7.31 %. Abstract : Caught the sun : Hollow porous iron pyrite nanoparticles were synthesized by a direct sulfurization of iron oxide derived from Prussian blue. The high efficiency of the hollow porous iron pyrite nanoparticles, as effective dye‐sensitized solar cell counter electrodes, was demonstrated with an efficiency of 7.31 %.